A Review on Review of Infant Feeding (International Journal of Food and Nutritional Sciences, 2022)
For almost all newborns, the greatest source of nourishment is their mother's milk. Breast milk offers a number of additional advantages as a biologic fluid, including regulation of postnatal intestine function, immunological ontogeny, and brain development. Although breastfeeding is strongly encouraged, it is not always feasible, appropriate, or sufficient. Infant formula is a commercially manufactured infant food replacement. Infant formula is made from cow's milk or soymilk and tries to replicate the nutritional content of breast milk as precisely as possible. There are many alternatives to cow's milk-based formula. We examine the nutritional content of breast milk and baby formulas in this article to get a better knowledge of the significance of nursing and the usage of infant formula from birth to 12 months of age when a replacement source of nourishment is needed.